Significant role of movies in efficacious teaching communicative competence (for the students of the English language departments) - Tsapro, G. Yu.; Yakuba, V. V. (Continuing Professional Education: Theory and Practice, 2019)
The article presents practical teaching techniques of using movies as an efficient teaching material that can motivate the 4th year students to practise their communication skills (both speaking and writing). Using movies can be a useful tool to help students to improve their proficiency in English as well as it can give them an opportunity to stimulate and develop their creative potential as future English teachers participating in classroom discussions, writing movie reviews and analysing them in class and also preparing communicative tasks for other students and acting as a teacher.